2019
DOI: 10.3366/cor.2019.0168
|View full text |Cite
|
Sign up to set email alerts
|

How native language and L2 proficiency affect EFL learners’ capitalisation abilities: a large-scale corpus study

Abstract: Capitalisation is a salient orthographic feature, which plays an important role in linguistic processing during reading, and in writing assessment. Learners’ second language (L2) capitalisation skills are influenced by their native language (L1), but earlier studies of L1 influence did not focus on learners’ capitalisation, and examined primarily ‘narrow’ samples. This study examines capitalisation error patterns in a large-scale corpus of over 133,000 texts, composed by nearly 38,000 EFL learners, who represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Most learners only had a single text in the sample (the mean number of texts per learner was 1.36 in the first subcorpus and 1.41 in the second). Multiple texts per learner were included to achieve sufficient coverage of the sample, in line with prior studies on the EFCAMDAT [e.g., 39 , 44 , 45 ]. See the “Sample information” document in the OSF repository for more details (under “Number of texts per learner”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most learners only had a single text in the sample (the mean number of texts per learner was 1.36 in the first subcorpus and 1.41 in the second). Multiple texts per learner were included to achieve sufficient coverage of the sample, in line with prior studies on the EFCAMDAT [e.g., 39 , 44 , 45 ]. See the “Sample information” document in the OSF repository for more details (under “Number of texts per learner”).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, note that past studies on the EFCAMDAT found L1 transfer effects on various other linguistic structures and phenomena, including clause subordination [46], relative clauses [47], clause-initial prepositional phrases [48], grammatical morphemes [49], articles [50], and capitalization [44]. X. Jiang et al even found evidence of lexical transfer on the usage rates of certain punctuation marks (e.g., dashes) and phrases (e.g., "to my mind") [48].…”
Section: Main Implicationsmentioning
confidence: 99%
“…Starting from the English reading corpus, Lee et al [2] studied the correlation between the English corpus and learners' mastery of vocabulary and solved the problem of vocabulary learning by encouraging learners to self-analyze and construct an English reading corpus [2]. Shatz [3] analyzed the role of capitalization in language processing and writing assessment during reading from the capitalization error patterns in an English reading corpus constructed from 133,000 texts of 38,000 foreign learners [3]. Guziurová [4] constructed an English reading corpus from English-type articles written by nonnative English-speaking research scholars and compared it with an English reading corpus constructed based on articles written by English writers designed by SciELF [4].…”
Section: Introductionmentioning
confidence: 99%